Corrigendum. (24th March 2017) - Unknown
Gamisch A. Notes on the Statistical Power of the Binary State Speciation and Extinction (BiSSE) Model. Evolutionary Bioinformatics 2016;12:165–174. (Original DOI:10.4137/EBO.S39732 )